S-equol status modulates skin response to soy isoflavones in postmenopausal women: results from a randomized placebo-controlled pilot trial - Vijayakumar, Vineetha; Climent, Eric; Enrique, María; Lamelas, Araceli; Álvarez, Beatriz; Chenoll, Empar; Naghibi, Malwina; Day, Richard (Frontiers in Nutrition, 2025)
Background/objectivesSoy isoflavones may benefit skin health in postmenopausal women, potentially via S-equol, a gut-derived metabolite with enhanced estrogenic and antioxidant activity.MethodsSixty-six postmenopausal women received either Novasoy®400 (n = 33), a soy isoflavone extract, or identical placebo (n = 33) for 12 weeks. Skin parameters, including crow’s feet and under-eye wrinkles, hydration, barrier function, and skin colour were assessed at baseline, D42 and D84. Urinary isoflavone metabolites, including S-equol, were measured at each time point.ResultsCrow’s feet wrinkle roughness decreased by 5.6% in the Novasoy®400 group versus a 1.6% increase in the placebo group, this difference was not statistically significant. However, urinary biomarker analysis identified 46.9% of women in the Novasoy®400 group and 15.6% in the placebo group as S-equol producers. In exploratory regression analysis limited to S-equol producers, higher urinary S-equol levels were significantly associated with improved under-eye wrinkle parameters and transepidermal water loss (TEWL) at D42. Multivariable model adjusting for age, soy intake, phototype and their interactions confirmed that older women experienced greater improvements in undereye wrinkles and barrier function in response to increased S-equol levels. Skin hydration showed a modest but statistically significant association with S-equol when combining data from both D42&84, indicating a potential cumulative effect.ConclusionSoy isoflavone supplementation increased urinary S-equol concentrations and was associated with improvements in under-eye wrinkle appearance, skin hydration, and barrier function—particularly among older postmenopausal women identified as S-equol producers. Findings suggest region-specific, time-sensitive effects dependent on S-equol levels.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT06047145, NCT06047145.